2023
DOI: 10.1101/2023.11.05.565728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes

Craig Liddicoat,
Robert A. Edwards,
Michael Roach
et al.

Abstract: Microbiomes are critical to the health and functioning of humans and ecosystems. Defining ‘healthy microbiomes’, however, remains elusive. More advanced knowledge exists on health associations for the compounds used or produced by microbes. Because microbes, their feedstocks and micro-environments interact synchronously, using functional genes to facilitate chemical transformations, this presents an intriguing opportunity to examine microbiomes through their potential to process compounds associated with human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…This aligns with findings in Liddicoat et al. ( 2023 ), who reported increased potential metabolism of acetate in more highly disturbed (compared to more mature and natural) plant–soil systems. Though we did not evaluate acetate in this study, future research could further examine the role of acetate in shaping urban greenspace soil microbial communities.…”
Section: Discussionsupporting
confidence: 92%
“…This aligns with findings in Liddicoat et al. ( 2023 ), who reported increased potential metabolism of acetate in more highly disturbed (compared to more mature and natural) plant–soil systems. Though we did not evaluate acetate in this study, future research could further examine the role of acetate in shaping urban greenspace soil microbial communities.…”
Section: Discussionsupporting
confidence: 92%
“…Soil bacterial communities are highly diverse and are involved in many ecosystem processes (e.g. nutrient cycling, soil formation, plant health) (Liddicoat et al, 2023;van der Heijden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While studies have reported higher soil bacterial heterogeneity across samples from remnant vegetation compared to cleared or urban lawns (Delgado-Baquerizo et al, 2021) and the occurrence of notable bacterial functional groups in soils (e.g. butyrate-producers) (Liddicoat et al, 2020(Liddicoat et al, , 2023Roslund et al, 2020), further research is needed to improve knowledge on how land cover type and factors such as light-dark cycles interact to influence soil bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation